2010
DOI: 10.1086/656624
|View full text |Cite
|
Sign up to set email alerts
|

Review of Hepatitis B Therapeutics

Abstract: There are currently seven approved therapies for chronic hepatitis B infection, an increase from just three agents five years ago. This review will focus on the pharmacology, potency, and adverse events associated with immunomodulatory agents and nucleos(t)ide analogs, with an emphasis on targets of therapy within the hepatitis B lifecycle. We will also offer guidelines for the use of available anti-HBV agents and review the emerging challenges in hepatitis B management, including HBV drug resistance, its mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 53 publications
0
69
0
Order By: Relevance
“…As a result, the use of tenofovir and lamivudine/emtricitabine is recommended as part of a HAART regimen for HBV/HIV co-infected patients. 20 Isolated anti-HBc is commonly associated with occult HBV infection. Mphahlele et al 11 reported an occult HBV prevalence of 33.3% in South Africans infected with HIV who had an 'anti-HBc only' serological picture.…”
Section: Original Articlesmentioning
confidence: 99%
“…As a result, the use of tenofovir and lamivudine/emtricitabine is recommended as part of a HAART regimen for HBV/HIV co-infected patients. 20 Isolated anti-HBc is commonly associated with occult HBV infection. Mphahlele et al 11 reported an occult HBV prevalence of 33.3% in South Africans infected with HIV who had an 'anti-HBc only' serological picture.…”
Section: Original Articlesmentioning
confidence: 99%
“…Our findings might reflect the real status among HIV infected adults on ART during the 2006-2010 study period as AIDS-related death still remained the leading cause of death among HIV infected patients. A review of 5612 HIV infected patients on ART over a period of 71 months in India reported that the majority of deaths (67%) were due to AIDS-related causes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) containing lamivudine (3TC) or emtricitabine (FTC) might initially suppress HBV, but HBV resistance can develop [14][15][16][17][18][19]. Additionally, immune reconstitution with ARV agents that suppress HIV replication can complicate HIV management by activating viral hepatitis (hepatic flare) in the absence of adequate HBV or HCV suppression [15].…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment strategies involving vaccines, interferons and nucleosides are unsatisfactory due to drug-resistance and adverse side effects [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, two new 6-C-boivinopyranosyl flavones together with three known analogues were isolated from Alternanthera philoxeroides (Figure 1), and their anti-HBV activities were evaluated toward HepG2 2.2.15 cells. 1 H-NMR showed an 6, 3′ (or 6, 4′) disubstituted luteolin structure (Table 1). According to the HMQC and HMBC spectra, the NMR chemical shifts of the carbons signals could be assigned unambiguously.…”
Section: Introductionmentioning
confidence: 99%